Morro da Conceição: space and the everyday life of place - Ferreira, Genovan Pessoa de Moraes (GEOUSP Espaço e Tempo (Online), 2000)
It's in a global society where local social contents tend to becom e empty and hom ogeneus, that we discuss what can survive as a unit of a social life of a neighbourhood. The most rem ote com m unity life took place based on strongly structured laces of identity in the natural pace of the place, where as nowadays neighbourhoods, under powerfull pressure of diverse and, not rarely strange, pace and content, struggle to resist to the threat of dilution creating their on identity in a perm anent local/global dialetics. This work attem pts to analyze Morro da C onceição, a poor neighbourhood in Recife. The main goal is to identify uses of space which lead to the endurance of the social relationships that caracterize the place, as well as, the contents which hintoricaly have shaped it. Through the multi-dim entional aspects of everyday life, of is innabitants we discuss spatial practices bases on use values which prom ote identity ties and the m aintenance of the place